Analysis of the Capital Adequate Ratio (CAR), Non-Performing Loans (NPL), and Return on Assets (ROA) Effect on Credit Distribution of Commercial Banks Listed on the Indonesia Stock Exchange - Syukriyah Syukriyah; Satia Nur Maharani; Dhika Maha Putri (AIBPM Publisher, 2020)
This research aims to determine the influence of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Return on Asset (ROA) effect on the Commercial Bank Credit Distribution. The population of this research is the 36 banking sector companies listed on the Indonesia stock exchange for the 2015-2018 period, the 30 companies among them chosen as the research sample. Analysis of data used in this research is multiple linear regressions. The result shows that the Capital Adequacy Ratio (CAR) gives a positive and significant influence on the Distribution of Credit. Meanwhile, Non-Performing Loan (NPL), and Return on Asset (ROA) give a negative and significant influence on the Distribution of Credit.